Māwardī and Augustine on Governance: How to Restrain the Restrainer? - Heck, Paul L. (Studies in Christian ethics, 2016)
According to the classical Muslim scholar Māwardī, rule is to bring about just order in society in accordance with God’s intentions. The state thus has a role in bringing about divine purposes, and yet Māwardī recognizes the flawed condition of humanity, the ruler included, making it vital that rule be based not solely on the divinely endowed agency of the ruler but more precisely on a set of rules meant to purge the soul of disordered inclinations. In that sense, there are grounds for drawing comparisons between Māwardī and Augustine.